The speeches of Fidel in Chile. Vol. II. - Oppenheimer, Martin (Quebec CA: Editions Latin America, 1972)
Recopila los discursos pronunciados por Fidel Castro en Chile en 1971.
Keywords: CHILE; CUBA; CASTRO RUZ, FIDEL; DISCURSOS